How much does an extreme rainfall event cost? Material damage and relationships between insurance, rainfall, land cover and urban flooding - Leal, Miguel (2019)
Miguel Leal was funded by the Portuguese Foundation for Science and Technology (FCT) through grant SFRH/BD/96632/2013. Marcelo Fragoso was financed by national funds through the FCT, under the framework of the project BeSafeSlide – Landslide early warning soft technology prototype to improve community resilience and adaptation to environmental change (PTDC/GES-AMB/30052/2017).